2011
DOI: 10.1016/j.aquatox.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on trace element accumulation in the early-life stages of squid Loligo vulgaris

Abstract: The anthropogenic release of carbon dioxide (CO(2)) into the atmosphere leads to an increase in the CO(2) partial pressure (pCO(2)) in the ocean, which may reach 950 μatm by the end of the 21st century. The resulting hypercapnia (high pCO(2)) and decreasing pH ("ocean acidification") are expected to have appreciable effects on water-breathing organisms, especially on their early-life stages. For organisms like squid that lay their eggs in coastal areas where the embryo and then paralarva are also exposed to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 69 publications
4
48
1
Order By: Relevance
“…Indirect maternal influence could be caused by a variation in the quality of the capsular and chorion membrane. Although this issue has not been explicitly studied, other investigators have found significant differences of Co uptake among capsules (one capsule of three capsules) of the squid, Loligo vulgaris [49]. Second, our findings show that the embryonic-statolith geochemistry is distinct for many elements among capsules, but not distinct for most elements among environmental treatments.…”
Section: Elemental Variations Among Treatment Groupsmentioning
confidence: 46%
See 4 more Smart Citations
“…Indirect maternal influence could be caused by a variation in the quality of the capsular and chorion membrane. Although this issue has not been explicitly studied, other investigators have found significant differences of Co uptake among capsules (one capsule of three capsules) of the squid, Loligo vulgaris [49]. Second, our findings show that the embryonic-statolith geochemistry is distinct for many elements among capsules, but not distinct for most elements among environmental treatments.…”
Section: Elemental Variations Among Treatment Groupsmentioning
confidence: 46%
“…The only other known study that tested the effects of environmental pH on squid-embryo statolith geochemistry found that only 65 Zn significantly differed from an elemental suite that included 110m Ag, 109 Cd, 57 Co, 203 Hg and 54 Mn [49]. Evidence that environmental tracers in squid statoliths can track seawater pH and [O 2 ] is especially useful, because uranium has been shown to be promising for understanding squid life history, migrations and habitat use [88,90,91].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations